Petrographic and mineralogical characterization of magmatic-hydrothermal breccia at Itatiaia alkaline complex, Rio de Janeiro state: occurrences of fluorite and REE minerals - Pires, Gustavo Luiz Campos; Bongiolo, Everton Marques; Neumann, Reiner; Ávila, Ciro Alexandre (Anuário do Instituto de Geociências, 2014)
The meso-cenozoic alkaline magmatism in Rio de Janeiro is represented by several plutonic/volcanic bodies, which occurred on W-E fracture and lineaments zones associated with the development of the Southeastern Brazilian Rift. One of main occurrences of those rocks is the Itatiaia Alkaline Complex (IAC), which consists of nepheline-syentite, dykes of trachyte/phonolite and magmatic-hydrothermal breccia. This paper shows petrographic and mineralogical caracterization (optical petrography, SEM-EDS and XRD analysis) of breccia. The breccia comprises lithoclasts of trachyte and cristaloclasts of biotite and K-feldspar immersed in microcrystalline groundmass. As hydrothermal mineral it were observed albite, carbonate, sanidine, clinochlore, pyrite (also in lithoclasts), biotite, apatite, fluorite, tourmaline, sericite, synchysite (À parisite), Nb-rutilo, sphalerite, epidote and orthoclase (adularia?). Minerals associated to weathering are gibbsite, melanterita and cancrinite. The new occurrences of fluorcarbonates (synchysite and parisite) and Nb-rutile at the IAC, are rare minerals commonly associated with hydrothermal alteration in alkaline-carbonatite complexes. The hydrothermal paragenesis, as well as comparison with data from other alkaline associations of Rio de Janeiro, suggests that the study rocks consist in late-magmatic/hydrothermal autobreccia, associated to epithermal systems of low sulphidation subtype and generated during interaction with low-temperature alkalic fluids. The description of fluorite and REE-minerals at IAC opens the possibility to find those minerals in other alkaline complex of Rio de Janeiro.